Effect of methyl methacrylate content on coatings' properties of palm oleic acid-based macromer - Ataei, S.; Yahya, Rosiyah; Gan, S.N. (Springer Verlag, 2011)
The macromer was synthesized using medium oil length oleic acid, phthalic anhydride, and glycerol. The synthesized macromer and methyl methacrylate (MMA) were copolymerized by free radical polymerization in toluene. The ratio between the macromer and MMA changed, and the effects on different properties of the copolymers, such as glass transition temperature (T g) and film properties, were studied. The macromer and copolymer structures were characterized by FTIR and 1H NMR spectroscopies. The coatings prepared with the highest ratio of MMA exhibited better overall physico-chemical properties. Alternatively, Tafel polarization curves showed that the corrosion rate value in NaCl solution decreases significantly when the MMA content is increased. Dynamic mechanical analysis results revealed that the increasing amounts of MMA lead to increasing T g values of copolymers.